2009
DOI: 10.1152/ajpendo.90938.2008
|View full text |Cite
|
Sign up to set email alerts
|

Oral bovine lactoferrin improves bone status of ovariectomized mice

Abstract: The aim of the present study was to evaluate the effect of dietary lactoferrin on bone metabolism in vivo using a postmenopausal animal model. We investigated whether bovine lactoferrin (bLF) ingestion could prevent bone loss in ovariectomized mice. Twelve-week-old female C3H mice either ovariectomized or sham operated were fed for 27 wk with the control diet (AIN-93M with 140 g of total milk protein as a protein source per kg of diet). Four groups of ovariectomized mice received diets including different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 60 publications
6
48
1
Order By: Relevance
“…Our results were consistent with those of previous studies [4,9,11] which indicated that dietary lactoferrin supplementation could have a beneficial effect on postmenopausal bone loss by modulating bone formation and resorption. Based on these results, it appears that promotion of bone formation and inhibition of bone resorption by bovine lactoferrin contributed to increased bone mineral density and composition of the distracted calluses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were consistent with those of previous studies [4,9,11] which indicated that dietary lactoferrin supplementation could have a beneficial effect on postmenopausal bone loss by modulating bone formation and resorption. Based on these results, it appears that promotion of bone formation and inhibition of bone resorption by bovine lactoferrin contributed to increased bone mineral density and composition of the distracted calluses.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies [4,9] showed that bovine lactoferrin increased the parameters of mechanical strength in a dose-dependent manner, and our results agreed with these findings. The above results support that oral administration of bovine lactoferrin contributed to the accelerated biomechanical strength of the distracted calluses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One week after the surgery, the Ovx rats were randomly divided into six groups of 10 rats each, as follows: Ovx untreated (Con); Ovx+17β-estradiol 0.1 mg·kg -1 ·week -1 , the positive control (E 2 ); Ovx+LF 10 mg·kg -1 ·d -1 (LF 1 ); Ovx+LF 100 mg·kg -1 ·d -1 (LF 2 ); Ovx+LF 1.0 g·kg -1 ·d -1 (LF 3 ); and Ovx+LF 2.0 g·kg -1 ·d -1 (LF 4 ). The doses of LF were chosen according to previous studies in the literature [21] .…”
Section: Methodsmentioning
confidence: 99%
“…In other animal species, information regarding lactoferrin is also reported. In a study reported by Blais et al (2009), bovine lactoferrin (bLF) was added to diets of ovariectonmized mice at a level of 1, 5, 10, 15 and 20 g/kg for 27 weeks, and it was shown that bLF improved bone mineral density (BMD) and femoral failure load in a dosedependent manner. These researchers also reported that addition of bLF to the culture medium at a level of 5 to 100 and 50 to 1000 μg/ml could improve growth and alkalin phosphatase activity of osteoblasts, respectively.…”
Section: Introductionmentioning
confidence: 99%